PROSES PEMBUATAN ARANG BATOK KELAPA DAN TULANG SAPI MENGGUNAKAN METODE PIROLISIS SEBAGAI MEDIA CARBURIZING - Tumpal Ojahan Ojahan; Miswanto Miswanto Miswanto; Slamtt Sumardi Sumardi (Jurnal Ilmiah Teknik Mesin POROS, 2021)
Fueled by a rise in food needs as beef and oil into basic commodities has been consumed by thepublic, has lead the increasing of waste the cows and coconut shell. The main ingredient used in thisresearch is a waste product from cow bones and from the remains of the coconut shells from which no orhousehold wastes, that can be processed into charcoal. The purpose of this research which is to enhanceeconomic value of waste from cow bones and coconut shells using combustion pyrolysis system beingcharred (fixed carbon) to produce good quality charcoal, to find out the extent of the temperature used andthe composition of charcoal. The process used in this research is pack carburizing with cow bones andcoconut shell as the media at the temperature 950oC, time detention three hours with variations compositioncharcoal. It can be concluded that charcoal bone across his cattle and charcoal coconut can be used as asource of carbon that might improve the force and hardness in the material carbon steel low (low carbonsteel). The process of pack carburizing can increase the value of % C, against low carbon steel material.